Expensive Political Costs in the 2024 Simultaneous Elections - Muhammad Misbahudholam Ar; Rofik Rofik; Ahmad Hanafi (International Forum of Researchers and Lecturers, 2023)
In Indonesia, the central issue of all elections is the management of election money. This issue creates various consequences for election administrators, voters, and voters, so increasing monetary policy practices also becomes a major issue in every election administration. The amount of money circulating in the 2024 election will likely increase from the 2019 legislative election. This is based on several factors. First, the electoral system and mechanism have not changed since 2019. This means that the personal side of elections, or the orientation of competition, still relies on candidates, not political parties. Second, the direction of the 2024 Pileg contestation is still based on the popularity and personality of the candidates. Third, to be elected, each candidate continues to try to increase his popularity, increase campaign activities, and finance himself.